Comparative Efficacy and Safety of Topical Calcineurin Inhibitors Versus Low-Potency Corticosteroids in Atopic Dermatitis: A Systematic Review and Meta-Analysis - Putri Indrasuari (Universitas Pendidikan Ganesha, 2026)
Atopic dermatitis is a chronic inflammatory skin disease commonly treated with topical corticosteroids, which are limited by adverse effects in sensitive areas. Topical calcineurin inhibitors have emerged as steroid-sparing alternatives. This study compares the efficacy and safety of topical calcineurin inhibitors versus low-potency topical corticosteroids in atopic dermatitis. A systematic review and meta-analysis of randomized controlled trials was conducted following PRISMA guidelines. PubMed, Cochrane Library, and ScienceDirect were searched. Outcomes included clinical efficacy and safety (skin atrophy and burning). Pooled risk ratios (RR) with 95% confidence intervals (CI) were calculated using a random-effects model. Six studies were included in this study. There was no significant difference in efficacy between groups (RR = 1.03, 95% CI: 0.80–1.32; p = 0.82; I² = 93%). Calcineurin inhibitors significantly reduced the risk of skin atrophy (RR = 0.12, 95% CI: 0.02–0.63; p = 0.01; I² = 0%). However, they were associated with a higher incidence of skin burning (RR = 3.08, 95% CI: 1.22–7.80; p = 0.02; I² = 97%). Calcineurin inhibitors provide similar efficacy with superior structural safety but lower tolerability due to increased local irritation. In conclusion, calcineurin inhibitors represent a safe and effective alternative to corticosteroids, particularly for sensitive areas and long-term management.